PERAN EKONOMI KREATIF DALAM MENINGKATKAN PENDAPATAN PEDAGANG (STUDI KASUS PADA PASAR YOSOMULYO PELANGI) - Pratiwi Esti Palupi; Jawoto Nusantoro; Ana Septiani (Universitas Muhammadiyah Metro, 2021)
This study aims to examine the Role of Creative Economy in Increasing Merchants Income at Pasar Yosomulyo Pelangi (PAYUNGI) Metro City. This research uses a descriptive qualitative approach. The sample of this research consisted of 29 people, namely Payungi Management, Traders and Visitors. To be able to obtain correct and accurate data so as to be able to answer research questions, the data collection techniques used in this study were observation, documentation and interviews. The technique used in this research uses descriptive qualitative research methods with reference to the concept, namely interactive models that clarify data analysis in three steps, namely, data reduction, data presentation, and drawing conclusions. The results of this study are the role of the Creative Economy at the Pasar Yosomulyo Pelangi (PAYUNGI) Metro City has a very important role.